The State of Digitization of Documentary Heritage in Scientific Libraries of Ukraine - Maryna Shevchenko; Alla Solianyk (Knygotyra, 2023)
Based on the survey results of the leading scientific libraries of Ukraine, the article reveals the current trends in the digitization of library collections. The authors explore the current state of search services for digitized documents by libraries; user access modes to digital copies of documents (public, restricted, local); the ways to register the users for access to full-text digital repositories. The necessity of adopting the National Program for Digitization of Documentation Heritage and its implementation at the corporate level is substantiated. Recommendations for improving the efficiency of digitization of documents by libraries of Ukraine, improving search tools and user-friendly access to digital repositories are given.